Development of commercial goat diet using low cost, locally available feed ingredients - Thanusan, S; Nawarathna KMCD; Jayaweera BPA (Eastern Journal of Agricultural and Biological Sciences, 2024)
This study was conducted to develop a commercial goat diet using locally available, low cost feed ingredients. The pelleted feed were prepared with 14% crude protein 2400 kcal/kg Digestible energy and 70% TDN according to NRC recommendations. The experiment was conducted for a period of 15 weeks providing other standard management practices. Eight weeks old (Body weight 20-23 kg) Jamnapari weaning male goats (n=4) were selected for the experiment. In first step, 5 pelleted feeds were prepared and economically low cost feed was used to the field trial using 4 male goats. The goats were randomly assigned to 02 different groups as treatment group T1 (with pelleted diet) and control group T2 (without pelleted diet) as one goat for control group and three goats for treatment group. The T1 group was fed with ad-libitum forages and prepared low cost pelleted feed in three times per day and T2 group was fed only with forages in same time per day. The data was collected for 60 days on palatability and body weight. Average daily gain of the animals and FCR were calculated and economical feasibility also was measured. There was a significant difference between treatment and control group for body weight gain after 60 days period (p>0.05), But no significant difference was recorded within treatment group (p<0.05). Thus it can be concluded that goats reared at pelleted diet had better nutrient intake and growth performances, suggesting its potential as an alternative diet to natural grass hay at the farmer’s management level as cost effectively